2015
DOI: 10.1111/jch.12662
|View full text |Cite
|
Sign up to set email alerts
|

Several Conventional Risk Markers Suggesting Presence of Albuminuria Are Weak Among Rural Africans With Hypertension

Abstract: The objective of this cross-sectional study was to investigate risk markers indicating the presence of albuminuria in patients with hypertension in rural sub-Saharan Africa (SSA). Urine albumin-creatinine ratio, glycated hemoglobin (HbA 1c ), blood pressure, anthropometry, and other patient characteristics including medications were assessed. We identified 160 patients with hypertension, of whom 68 (42.5%) were codiagnosed with diabetes mellitus (DM Only dysregulated DM and age were the conventional risk marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
1
1
Order By: Relevance
“…This does not agree with findings from other studies. One such study in an African setting [ 32 ] showed that treatment with calcium channel blockers was associated with microalbuminuria, although our study did not show an association. The questions on medications require a separate study as our study was not powered to answer these questions.…”
Section: Discussioncontrasting
confidence: 96%
“…This does not agree with findings from other studies. One such study in an African setting [ 32 ] showed that treatment with calcium channel blockers was associated with microalbuminuria, although our study did not show an association. The questions on medications require a separate study as our study was not powered to answer these questions.…”
Section: Discussioncontrasting
confidence: 96%
“…In this issue of The Journal of Clinical Hypertension , Rasmussen and colleagues from the University of Copenhagen present their investigation on risk markers for albuminuria in patients with hypertension in rural sub‐Saharan Africa (SSA). Exclusion criteria included a positive urine dipstick for nitrites, leukocytes, blood, or fever.…”
mentioning
confidence: 99%